Breaking seed dormancy in smooth loofah (Luffa cylindrica (L.) M. Roem.) using scarification and dry heat treatment - Chaodumrikul, Sajee; Kaewsorn, Pichittra; Chulaka, Pariyanuj; Chanprasert, Wanchai (Agriculture and Natural Resources, 2016)
Hard seed dormancy is a common problem with smooth loofah seed. Scarification, clipping and dry heat were used to break dormancy in smooth loofah seed at the Department of Horticulture, Kasetsart University, Bangkok, Thailand. A completely randomized design with 20 treatments was used involving: untreated seed (control), clipping, scarifying by scarifier at 40, 70 and 100 revolutions per minute (rpm) for 1 min, and dry heat at 60 oC, 70 oC and 80 oC for 1-5 h. After breaking dormancy, seed germination was tested in four replicates, with 50 seeds per replicate. The thickness of the seed coat was measured under a digital microscope. The results showed that clipped seeds gave the highest germination (100%) and decreased mean germination time (3.58 d). Scarified seed using a scarifier at 70 and 100 rpm for 1 min resulted in germination rates of 67.0-75.5%, which was higher than for seeds scarified at 40 rpm. The dry heat-treated seeds at 60 oC for 3-5 h and at 70 oC for 2-5 h had germination of 71.0-80.5%. The outer layer of seed coat scarified at 100 rpm for 1 min was thinner than those of un-scarified seed samples. Dry heat had no effect on the seed coat thickness, but affected cells of the inner seed coat as the sclerenchymous cells showed disordered characteristics and were non-uniform and seemed to have been torn off. Dry heat treatment and scarification significantly improved germination compared to the control treatment. However, 80% germination may not be considered as an effective method at a commercial scale where 100% germination is needed. Further investigation of more accessions that may have different seed coat thicknesses may be needed.